Dependability of networked computer-based systems - Verma, A. K. (Ajit Kumar); Srividya, Ajit.; Kumar, Manoj; SpringerLink (Online service). (London New York Springer, 2011)
The measurement of dependability attributes on real systems is a very time-consuming and costly affair, making analytical or simulation modeling the only viable solutions. Dependability of Networked Computer-based Systems explores reliability, availability and safety modeling of networked computer-based systems used in life-critical applications such as avionics, nuclear power plants, automobiles and chemical process industries. Dependability of Networked Computer-based Systems gives an overview of basic dependability modeling concepts and addresses new challenges in dependability modeling of networked computer-based systems, as well as new trends, their capabilities and limitations. It covers a variety of dependability modeling methods: stochastic processes, Markov and semi-Markov models, response-time distribution, stochastic Petri-net-based modeling formalisms, and Monte Carlo simulation models. Dependability of Networked Computer-based Systems provides students and researchers with a detailed overview of dependability models and analysis techniques. Practicing engineers will also find this text a useful guide to decision-making based on system dependability at the design, operation and maintenance stages.
Introduction -- Probability theory -- Stochastic processes and models -- Dependability models of computer-based systems -- Network technologies for real-time systems -- Response-time models and timeliness hazard rate -- Dependability of networked computer-based systems -- Appendix A : MATLAB codes.
Electronic reproduction.
Keywords: Computer networks -- Reliability; Electronic books